Health returns to education by family socioeconomic origins, 1980-2008: Testing the importance of gender, cohort, and age - Matthew A. Andersson (Elsevier, 2016)
Recent studies find that health returns to education are elevated among those who come from disadvantaged families. These findings suggest that education may be a health resource that compensates or "substitutes" for lower parental socioeconomic status. Alternatively, some studies find support for a cumulative (dis)advantage perspective, such that educational health returns are higher among those who already were advantaged, widening initial health (dis)advantages across the life course. However, it remains unclear whether these findings are dependent on gender or cohort, and this is a fundamental oversight given marked differences between men and women in educational and health inequalities across the twentieth century. Drawing on national US data (1980-2002 General Social Survey with 2008 National Death Index Link), I indeed find that the presence or strength of resource substitution or cumulative (dis)advantage depends upon health measure as well as gender and cohort. For self-rated health, cumulative (dis)advantage explains educational health disparities, but among men only. Cumulative (dis)advantage in avoiding fair or poor health is partly explained by cohort and age variation in health returns to education, and cumulative (dis)advantage in excellent health is more robust in earlier cohorts and at older ages. For mortality, resource substitution is instead supported, but for women only. Among those from disadvantaged families, educational mortality buffering increases with cohort but diminishes with age. Taken together, these findings confirm prior research showing that adult health inequalities linked to education depend on family background, and extend this work by demonstrating that the nature and extent of these dynamics differ considerably depending on the health outcome being assessed and on an individual's historical context, life course stage, and gender. Keywords: Self-rated health, Mortality, Education, Gender, Cohort, Age